A Comparative Study of Urine Protein Analysis Using Urine Dipstick Testing and Laboratory Results in School-Age Children with Nephrotic Syndrome - Pliansee, Kamonwan; Rojnawee, Suwimon (Thai Red Cross Nursing Journal, 2024)
The objective of this study was to compare the differences in urine protein when testing with a urine dipstick with results obtained in a hospital laboratory. The sample group consisted of school-age children diagnosed with nephrotic syndrome for at least 3 months at the outpatient department of a university hospital, the Thai Red Cross. A total of 65 willing and cooperative participants, including parents and school-age patients, were involved in the investigation. The research tools included a demographic data questionnaire and urine dipstick testing. Data were analyzed using descriptive statistics and chi-square test. The research findings indicated no statistically significant difference between the results of urine protein testing with the dipstick and those from the hospital laboratory (X2=188.28, p-value<0.01). The study reflects the efficiency of a urine dipstick in analyzing urine protein among school-age children with nephrotic syndrome. Nurses and parents can employ this technique for monitoring urine protein and observing recurrent symptoms in this patient group. This method is rapid, convenient, economical, and can contribute to decreasing the waiting time for laboratory results, thereby contributing to the advancement of pediatric patient care through telemedicine.